2014
DOI: 10.1002/bjs.9534
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after implementation of a multimodal standard care pathway for laparoscopic colorectal surgery

Abstract: Compliance with an enhanced recovery pathway was associated with less opiate use, fewer complications and a shorter hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 121 publications
(89 citation statements)
references
References 43 publications
2
84
3
Order By: Relevance
“…Multimodal pain regimens that include gabapentin, NSAIDs, acetaminophen, and regional anesthesia were effective in controlling perioperative pain and decreasing perioperative opioid use following arthroplasty surgery [74,75]. The literature has highlighted the need for studies focused on multimodal analgesic protocols for colorectal [76], thoracic, amputation, mastectomy [77], orthopaedic [37], and liver resection surgeries [65]. In these trials, the outcome of interest should not only focus on reducing acute postoperative pain and opioid consumption (due to the immediate drug effect), but also on ascertaining whether preventive effects that reduce the incidence and severity of CPSP are demonstrated.…”
Section: Multimodal Analgesiamentioning
confidence: 99%
“…Multimodal pain regimens that include gabapentin, NSAIDs, acetaminophen, and regional anesthesia were effective in controlling perioperative pain and decreasing perioperative opioid use following arthroplasty surgery [74,75]. The literature has highlighted the need for studies focused on multimodal analgesic protocols for colorectal [76], thoracic, amputation, mastectomy [77], orthopaedic [37], and liver resection surgeries [65]. In these trials, the outcome of interest should not only focus on reducing acute postoperative pain and opioid consumption (due to the immediate drug effect), but also on ascertaining whether preventive effects that reduce the incidence and severity of CPSP are demonstrated.…”
Section: Multimodal Analgesiamentioning
confidence: 99%
“…Mathiesen et al demonstrated significantly reduced opioid consumption and associated side effects as well as improved postoperative mobilization in patients undergoing multilevel spine surgery following the implementation of a comprehensive multimodal treatment paradigm [73]. Similar findings have also been reported in the general surgery literature [74][75][76].…”
Section: Proxies For Measuring Pain Management Resultsmentioning
confidence: 53%
“…Multimodal analgesia has been successfully implemented into multiple surgical pathways, and has been shown to reduce opioid consumption (38), surgical complications (38,39), and length of hospital stay (38,39,40). Some agents that have been used successfully in multimodal pathways include acetaminophen (PO and IV), cyclooxygenase-2 (COX-2) inhibitors, gabapentinoids (gabapentin and pregabalin), non-steroidal anti-inflammatory drugs (NSAIDs), glucocorticoids, local anesthetics, α-2 agonists (clonidine and dexmedetomidine), and ketamine (Table 3).…”
Section: Multimodal Approach To Postoperative Analgesiamentioning
confidence: 99%